Modul Digital Berbasis Problem Based Learning: Solusi Inovatif Pembelajaran Materi Sel dengan Canva - Fheny Friscasadin Ilyas; Rahmatia Thahir; Anisa Anisa (Mathematics Education Study Program, 2025)
This type of research is Research and Development. The aim of this research is to determine the validity and practicality of digital module teaching materials based on problem based learning using Canva on cell material. The population in this study were students at SMA Muhammadiyah 6 Makassar with the selected sample being class XI Science at SMA Muhammadiyah 6 Makassar. The data collection technique is by using a validity and practicality assessment questionnaire. The data collected is data regarding the validity and practicality of the teaching materials developed. The results of the validity analysis show that the digital module teaching materials based on problem based learning using Canva in the cell material developed obtained a score of 0.9 which is in the very valid category. Meanwhile, the results of the practicality analysis from the teacher obtained a score of 81% which was in the range 80% < P < 100% with the very practical category and the results of the student questionnaire analysis obtained a score of 77% which was in the range 60% < P < 80% with the practical category So it can be concluded that the digital module teaching materials based on problem based learning using Canva in cell material are valid and practical. Keywords: digital module, Problem Based Learning ,Canva